The Processing of Non-Anticipated Information in Financial Markets: Analyzing the Impact of Surprises in the Employment Report - Hautsch, Nikolaus; Hess, Dieter (Review of Finance, 2002)
Abstract This paper delineates the simultaneous impact of non-anticipated information on mean and variance of the intraday return process by including appropriate variables accounting for the news flow into both the mean and the variance function. This allows us to differentiate between the consistent price reaction to surprising news and the traders' uncertainty about the precise price impact of this information. Focussing on the US employment report, we find that headline information is almost instantaneously incorporated into T-bond futures prices. Nevertheless, large surprises, and ‘bad’ news in particular, create considerable uncertainty. In contrast, if surprises in related headlines cross-validate each other, less room for differences of opinion is left and hence volatility is decreased. JEL classification codes: E44, G14.